2004
DOI: 10.7589/0090-3558-40.4.804
|View full text |Cite
|
Sign up to set email alerts
|

Leucocytozoon lovati Infections in Wild Rock Ptarmigan (Lagopus mutus) in Japan

Abstract: Leucocytozoon lovati infections were detected in free-flying rock ptarmigan (Lagopus mutus), an endangered species that inhabits alpine areas in Japan. Eight of nine adult birds tested positive for L. lovati infection. For comparison, two captive rock ptarmigans hatched in a breeding facility at the foot of the mountains were examined. Both were negative for L. lovati infection. This is the first report of L. lovati infection in the rock ptarmigan in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Calculation of the infection rate: For evaluating the parasitemia, we used the Ashford Scale [2,10]. This scale is described as follows: grade 0, no infected cells are observed in any of the fields under × 100 magnification; grade 1, less than one infected cell is observed in 100 fields under × 400 magnification; grade 2, 1-10 infected cells are observed in 100 fields under × 400 magnification; grade 3, 11-100 infected cells are observed in 100 fields under × 400 magnification; grade 4, more than 100 infected cells are observed in 100 fields under × 400 magnification.…”
Section: Number Of Birds Surveyedmentioning
confidence: 99%
See 4 more Smart Citations
“…Calculation of the infection rate: For evaluating the parasitemia, we used the Ashford Scale [2,10]. This scale is described as follows: grade 0, no infected cells are observed in any of the fields under × 100 magnification; grade 1, less than one infected cell is observed in 100 fields under × 400 magnification; grade 2, 1-10 infected cells are observed in 100 fields under × 400 magnification; grade 3, 11-100 infected cells are observed in 100 fields under × 400 magnification; grade 4, more than 100 infected cells are observed in 100 fields under × 400 magnification.…”
Section: Number Of Birds Surveyedmentioning
confidence: 99%
“…Recent studies have found that Japanese rock ptarmigans are infected with Leucocytozoon lovati [10]. Infection with these hematozoan parasites is reported to be prevalent in wild ptarmigans and grouses in the Palearctic and Nearctic regions [3], and the infection in the Japanese rock ptarmigan indicates the distribution of L. lovati in the lower latitudes.…”
mentioning
confidence: 98%
See 3 more Smart Citations